Pengaruh Bauran Pemasaran 7P Terhadap Loyalitas Pelanggan Yang Dimoderasi Kepuasan Pelanggan Pada Pengunjung Wisata Pantai Tapandullu Kabupaten Mamuju: The Influence of 7P Marketing Mix On Customer Loyalty Which Is Moderated By Customer Satisfaction In Tapandullu Beach Tourist Visitors, Mamuju District - Muchtar Muchtar; Muhammad Aqsa; Hudyah Astuti Sudirman (School of Business, Bogor Agricultural University (SB-IPB), 2024)
The development of the tourism industry continues to run very rapidly, so special attention is needed to maximize every potential that exists so that the number of tourists visiting is increasing. One of them is by utilizing the marketing mix in increasing the number of tourists. In line with that, this study aims to test the 7p marketing mix of customer loyalty, by making the satisfaction variable a mediator variable. The use of data types in this study is primary data, interview techniques and questionnaire distribution were used to obtain data in this study. The sampling technique uses convenience sampling. The sample in this study amounted to 170 respondents visitors to Tapandullu Beach Tourism, data processing with the help of SmartPLS. To answer the research objectives, the SmartPLS Output showed findings that positively and significantly the 7p marketing mix affects customer loyalty. However, in customer satisfaction, the marketing mix does not have a significant effect on the direction of positive influence, this is due to the lack of facilities to support the comfort of visitors in order to create a sense of satisfaction and loyalty. Customer satisfaction has a unidirectional and meaningful relationship with loyal customers, the marketing mix has a unidirectional and meaningless influence directly on loyal customers and moderated satisfied customers as a mediator variable in Tapandullu Beach Tourism Mamuju Regency. Keywords: marketing mix 7p, customer satisfaction, customer loyalty, tourism industry, tapandullu beach